ALK inhibitors in non-small cell lung cancer: the latest evidence and developments. (January 2016) - Sullivan, Ivana; Planchard, David
The treatment of patients with advanced non-small cell lung cancer (NSCLC) harbouring chromosomal rearrangements of ALK (anaplastic lymphoma kinase) was revolutionized by crizotinib, a small molecule inhibitor of ALK, ROS1 and MET . Unfortunately, the disease progressed within the first 12 months in most of the patients because of the development of crizotinib resistance in the majority of patients and the emergence of acquired resistance mutations in most of them. Many of them had been reported even before its approval leading to the rapid development of second-generation ALK inhibitors for crizotinib-resistant NSCLC. In the last few years, novel potent ALK inhibitors with promising results and a good toxicity profile have become available: ceritinib (LDK378), alectinib (RG7853/AF-802/RO5424802/CH5424802), brigatinib (AP26113), entrectinib (RXDX-101, NMS-E628), PF-06463922, ASP3026, TSR-011, X-376/X-396 and CEP-28122/CEP-37440. Moreover, HSP90 (90 kDa heat shock protein) inhibitors have demonstrated clinical activity in patients with ALK+ NSCLC. This review focuses on the molecular and clinical properties of this new generation of ALK inhibitors under development in the clinic.